The making of the Chinese society in Perak, 1874-1941 / Tan Ai Boay - Tan, Ai Boay (2015)
This dissertation examines the making of the Chinese society in Perak. It scrutinizes the Chinese migration from South China, how the migrants adapted to the local society, and whether localisation had occurred among the Chinese migrant community in Perak before the Second World War. The objectives of this thesis include: firstly, to probe into the formation of the Chinese community in Perak and the turning point of their transformation; secondly, the study of the transitional pattern of Chinese leadership in Perak; thirdly, the scrutiny of the contestations between the British and the Chinese governments for the loyalty of the Chinese community in Perak; and lastly, to trace the growth of Chinese schools and organizations, and to find the turning point of such development. Besides conducting a search in the library and archival materials in Malaysia, Great Britain, Singapore and Taiwan, the research had also accumulated primary materials, such as the epigraphic materials in Chinese temples and cemeteries, by carrying out field work in Perak and Penang. In addition to that, the research also employed oral history as a part of the research methodology. Eventhough the Chinese in Perak were generally influenced by the political movements in China, they had learned to adapt themselves to the political and social climate of their adopted country. Thus the adopted country became their home land. The research concludes that elements of localisation could be traced back to the period before World War Two.